Barriers and enablers of access to diabetes eye care in Auckland, New Zealand: a qualitative study - David Squirrell; Matire Harwood; Jacqueline Ramke; Corina Grey; Rinki Murphy; Pushkar Raj Silwal; Maryam Pirouzi (BMJ Open)
Objective To explore the barriers and enablers to accessing diabetes eye care services among adults in Auckland.Design This was a qualitative study that used semistructured interviews. We performed a thematic analysis and described the main barriers and enablers to accessing services using the Theoretical Domains Framework.Setting The study took place in two of the three public funding and planning agencies that provide primary and secondary health services in Auckland, the largest city in Aotearoa New Zealand.Participants Thirty people with diabetes in Auckland who had experienced interrupted diabetes eye care, having missed at least one appointment or being discharged back to their general practitioner after missing several appointments.Results We identified barriers and enablers experienced by our predominantly Pacific and Māori participants that aligned with 7 (of the 14) domains in the Theoretical Domains Framework. The most reported barriers were transport issues, lack of awareness regarding the importance of retinal screening, time constraints, limited and/or inflexible appointment times and competing family commitments. Enablers included positive interactions with healthcare providers and timely appointment notifications and reminders.Conclusions Diabetes eye services could be made more responsive by addressing systemic barriers such as service location and transport links, appointment availability and meaningful information to aid understanding.